Kedaulatan Rakyat dalam Pemilihan Umum Legislatif - Mustajib Mustajib (Fakultas Hukum Universitas Islam Jember, 2018)
People’s Consultative Assembly (MPR) RI is a form of popular sovereignty. Amendments or changes to Article 1 (2) of Indonesia’s 1945 Constitution (UUD 1945) conducted during the reform initiated in 1998 has brought a lot of implications, particularly with regard to the role of the People's Consultative Assembly (MPR), which before the amendments of Constitution of the Republic of Indonesia Year 1945 (UUD 1945), is the highest state body. As the highest state institutions, the Assembly has the authority to supervise the President and give tasks to the President through the outlines of state policy. After the amendments of Constitution of the Republic of Indonesia Year 1945 (UUD 1945), particularly the amendment of Article 1 (2), there is the impression the president no longer had a bow in implementing the government. The vagueness of the people as sovereign representation of the highest in the country as stated in Article 1 (2) will be a serious impact on the implementation and administration of the state, even to the future of the nation. It is time to the amendment of Article 1 (2) Constitution of the Republic of Indonesia Year 1945 (UUD 1945) shall be re-examined. Keywords : Sovereignty, People’s Consultative Assembly, Amendments.